Global Evaluation of Medical College Admission: The Policies and Procedures - Syed Zulfiqar Ali Shah,; Pireh,; Dua Bukhari,; Muqadas Fatima,; Sahar Fatima Sirhindi,; Raheela Kumbhar, (Pakistan Journal of Medical & Health Sciences, 2024)
The medical & dentistry college entrance test is an annual paper-based examination administered in Pakistan and overseas for those seeking undergraduate medicine and dentistry studies in Pakistan. It is required for admittance to all professional and dentistry institutions, public as well as private, in Pakistan.The Pakistan medical and dental council conduct the medical entrance test yearly. In 2020, the examination replaced the previously administered regional medical admission assessments. In 2023, after the demise of the PMC, the examination is elevated to a regional level, necessitating every province to select a college or university to administer the MDCAT exam. In the USA and some medical schools in Canada as well, medical education occurs at the level of postgraduate study, necessitating a first degree with an appropriate cumulative grade point average for admission into a medical education program